Evaluation of seawater exposure on mechanical properties and failure behavior of E-Glass/BMI composite for marine use - Zhao, Yian (2018)
Since composite material is playing an increasingly important role in the marine and offshore drilling industry, it is essential to have a good understanding on degradation of the material in the seawater environment. This study investigates the influence of seawater exposure on the mechanical and failure behavior of E-Glass/BMI composite. The water diffusion behavior in the composite has been studied through immersing the specimens in seawater under different conditions. The diffusion rate accelerates with increase of temperature, and the material shows irreversible damage due to seawater absorption at the temperature of 80°C. It is also found that external stress would significantly increase the water absorption. The water uptake in the specimen at 50°C showed a two stage behavior dominated by Fickian law and polymeric relaxation respectively, and saturation was not achieved in 8 months. After diffusion, the Tg of the material is considerably lowered due to plasticization effect. However the effect was found to be reversible after drying the specimen. Based on the testing results of tensile, flexure and fatigue properties of the composites, it is concluded that seawater exposure especially at elevated temperature leads to significant degradation on mechanical properties of the composite. However, the flexural strength of BMI composite with seawater absorption becomes less susceptible to temperature change. It is also found that the seawater absorption doesn't show significant effect on the stiffness of the material.